Effects of anodal tDCS on motor and cognitive function in a patient with multiple system atrophy. Issue 6 (12th March 2020) - Alexoudi, Athanasia; Patrikelis, Panayiotis; Fasilis, Theodoros; Deftereos, Spyros; Sakas, Damianos; Gatzonis, Stylianos
Abstract: Purpose: Multiple system atrophy (MSA) is a progressive neurodegenerative disease characterized by postural instability, autonomic failure, cerebellar ataxia, and cognitive deficits. There is currently no effective cure. Transcranial direct current stimulation (tDCS), offers promise in amendment of motor, and cognitive performance in advanced Parkinson's disease. Case description: We estimated the effect of anodal tDCS on motor and cognitive function in a 66-year-old woman with moderate MSA. For the evaluation of the motor function, we used the Unified MSA Rating Scale II, the Unified Parkinson's Disease Rating Scale Part III (UPDRS III), and the Timed Up and Go test (TUG). The battery of neuropsychological tests included the Rey's Auditory Verbal Learning Test (RAVLT) and the Digit Symbol Substitution Test-Wechsler Adult Intelligence (DSST-WAIS-III), the Trail Making Test (TMT-A). tDCS was applied in 10 sessions. Clinical evaluations were performed at baseline, day 11, day 30, and at day 90. Results: Anodal stimulation was associated with improvement in UPDRS III and the TUG test. A positive effect was also seen in RAVLT the DSST-WAIS-III and the TMT-A. Conclusions: Our results suggest that tDCS has a beneficial effect mainly on motor performance in MSA, which lasts beyond the duration of the treatment. Implications for rehabilitation: Multiple system atrophy is a progressive neurodegenerative disease characterized by postural instability, motor, and cognitive deficits. Transcranial direct current stimulation offers promise in amendment of motor and cognitive performance in advanced Parkinson's disease. Stimulation was associated with significant improvement in Unified Parkinson's Disease Rating Scale Part III and the Timed Up and Go test. A positive effect was also seen in auditory-verbal memory and learning in working memory and in visuomotor activity and processing speed. Transcranial direct current stimulation has a beneficial effect mainly on motor performance, which lasts beyond the duration of the treatment.